CHARACTERIZATION OF ANTISOCIAL PERSONALITY OF MAIN CHARACTER IN TOBA DREAMS - Apriwinda, Priskilla; Putri, Citra Anggia; Damanik, Sisila Fitriany (TRANSFORM: Journal of English Language Teaching and Learning, 2020)
This study deals with the characterization of Ronggur as the main character in Toba Dreams Movie and it was aimed to knowing the characteristics of antisocial personality of Ronggur in the movie. It was conducted by applying descriptive qualitative method. The source of the data was taken from Toba Dreams movie and the data were which showed actions and dramatic statements from Ronggur and other characters in the movie. The findings of the study showed that the characteristics of antisocial personality of Ronggur are : (1) failure to conform to social norms and respect lawful behaviours with 2 items, (2) deceitfulness with 10 items, (3) impulsivity with 5 items, (4) irritability with 33 items, (5) reckless disregard for the safety of self or others with 7 items, (6) Lack of Remorse with 3 items. The method of characterization and antisocial characteristics used on the main character in Toba Dreams have different meaning. Which in Robert & Jacobs theory of characterization methods presents antisocial personality characteristics, whereas in Schwartz theory antisocial characteristics apply to see the depiction of antisocial personality.